(untitled) (Global Journal of Human-Social Science, 2024)
While battles battering the battered the most or worst is a run-of-the-mill story the gift and not the gun destroying them is rather a rare tale in the human civilization when it comes to the modern history of all six isolated aboriginal ethnic tribes of Andaman and Nicobar archipelago the Indian islands in Bay of Bengal However it is no less good save in the biocultural survival of one of those ethnic communities the fiercely hostile Sentinelese of North Sentinel Island by way of rescripting its cultural story through the instrumentality of the Government s decision initiated and pushed through by the author - who had befriended this truculent tribe in 1991 - to terminate the practice of hankering to placate and cultivate the animus natives by gift giving through contact expeditions Consequently enabling the Sentinelese before it is too late to revert to their age-old ferocity towards outsiders since that being the most efficacious self-protective cover and thus averting its decimation fall from the Golden Age Though the term golden age is generally used metaphorically the modern archeologists employ it to describe the pre-agricultural societies while the anthropologists ascribe it to depict the story of the primordial hunters and gatherers The existing four Negrito ethnic communities of Andaman Islands lived their golden age for more than 50 000 years i e ever since their ancestors came here from Africa while the two surviving Mongoloid tribes of Nicobar Islands did it for nearly 14 000 years i e from the time their progenitors arrived from South- East Asia Perhaps without a premonition five of these aboriginal communities lost their golden age one by one to the outlanders primarily not because of the onslaught but due to the gift offerings made by the interlopers The gifts by nonautochthons have been proved to be the Trojan Horse in the Troy of the autochthons of A N Islands